The role of a trigeminal sensory nucleus in the initiation of locomotion - Buhl, Edgar (Blackwell Science Inc, 2012)
While we understand how stimuli evoke sudden, ballistic escape responses, like fish fast-starts, a precise pathway from sensory stimulation to the initiation of rhythmic locomotion has not been defined for any vertebrate. We have now asked how head skin stimuli evoke swimming in hatchling frog tadpoles. Whole-cell recordings and dye filling revealed a nucleus of ∼20 trigeminal interneurons (tINs) in the hindbrain, at the level of the auditory nerve, with long, ipsilateral, descending axons. Stimulation of touch-sensitive trigeminal afferents with receptive fields anywhere on the head evoked large, monosynaptic EPSPs (∼5–20 mV) in tINs, at mixed AMPAR/NMDAR synapses. Following stimuli sufficient to elicit swimming, tINs fired up to six spikes, starting 4–8 ms after the stimulus. Paired whole-cell recordings showed that tINs produce small (∼2–6 mV), monosynaptic, glutamatergic EPSPs in the hindbrain reticulospinal neurons (descending interneurons, dINs) that drive swimming. Modelling suggested that summation of EPSPs from 18–24 tINs can make 20–50% of dINs fire. We conclude that: brief activity in a few sensory afferents is amplified by recruitment of many tINs; these relay summating excitation to hindbrain reticulospinal dINs; dIN firing then initiates activity for swimming on the stimulated side. During fictive swimming, tINs are depolarised and receive rhythmic inhibition but do not fire. Our recordings demonstrate a neuron-by-neuron pathway from head skin afferents to the reticulospinal neurons and motoneurons that drive locomotion in a vertebrate. This direct pathway, which has an important amplifier function, implies a simple origin for the complex routes to initiate locomotion in higher vertebrates.